1992
DOI: 10.1172/jci116145
|View full text |Cite
|
Sign up to set email alerts
|

CD10/neutral endopeptidase 24.11 in developing human fetal lung. Patterns of expression and modulation of peptide-mediated proliferation.

Abstract: The cell membrane-associated enzyme CD10/neutral endopeptidase 24.11 (CD10/NEP) functions in multiple organ systems to downregulate responses to peptide hormones. Recently, CD10/NEP was found to hydrolyze bombesin-like peptides (BLP), which are mitogens for normal bronchial epithelial cells and small cell lung carcinomas. Growth of BLP-responsive small cell lung carcinomas was potentiated by CD10/NEP inhibition, implicating CD10/NEP in regulation of BLP-mediated tumor growth. BLP are also likely to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 44 publications
2
58
0
1
Order By: Relevance
“…We performed additional experiments treating newborn mice with GRP, NMB, and a synthetic BRS3 ligand, (DTyr 6 ,[R-Apa 11 , Phe 13 , Nle 14 ]Bombesin- [6][7][8][9][10][11][12][13][14]) (31), using doses that are equimolar to 200 g/kg bombesin (detailed in the online supplement). GRP has the same effects on alveolarization as bombesin ( Figure 6F).…”
Section: Alveolarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed additional experiments treating newborn mice with GRP, NMB, and a synthetic BRS3 ligand, (DTyr 6 ,[R-Apa 11 , Phe 13 , Nle 14 ]Bombesin- [6][7][8][9][10][11][12][13][14]) (31), using doses that are equimolar to 200 g/kg bombesin (detailed in the online supplement). GRP has the same effects on alveolarization as bombesin ( Figure 6F).…”
Section: Alveolarizationmentioning
confidence: 99%
“…BLP can promote growth and maturation of developing fetal lung in humans, nonhuman primates, rats, and mice (8)(9)(10). Levels of GRP receptor (GRPR) and GRP mRNAs peak during the canalicular phase, then fall to much lower levels during normal alveolarization after birth (8,11).…”
mentioning
confidence: 99%
“…CD10, also known as the common acute lymphocytic leukemia antigen (CALLA) or neutral endopeptidase, is a cellsurface zinc metalloendopeptidase (1,2). The ability of CD10 to cleave signal peptides at the cell surface can affect cell proliferation, differentiation, and migration (2)(3)(4). Expression of CD10 can be used as a diagnostic marker for a variety of cancers (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…2 Supported by National Institutes of Health NHLBI Hematology Training Grant T32 HL007501. 3 Supported by a pre-doctoral fellowship from the National Science and Engineering Research Council of Canada. 4 Supported by an undergraduate award from the Beckman Foundation Scholars Program.…”
mentioning
confidence: 99%
“…21 Thus, NEP contributes to the maintenance of a delicate balance of neuropeptides in the lung and elsewhere; disruption of that balance could alter susceptibility to hypoxic injury. 22,23 The role of NEP in chronic hypoxic PHTN remains uncertain. Early studies, conducted with inhibitors of NEP, suggested that this peptidase may contribute to chronic hypoxic PHTN.…”
mentioning
confidence: 99%